PERSEPSI MASYARAKAT KECAMATAN PAMIJAHAN TERHADAP PENERAPAN HALAL TOURISM - Sartika Resliana; Ujang Buchori Muslim; Hasbi Ash Shiddieqy (SAHID BUSINESS JOURNAL, 2021)
ABSTRACT With the plan develop halal tourism, it will cause various kinds of public perceptions regarding conceptual understanding, government regulations, potensials and challenges. The purpose of this study wa to analyze the percecptions of the Pamijahan District Community on the application of halal tourism. Rhis type of research is using quantitative research using a Likert Scale, with a sample size of 75 respondents. The sampling technique used is the random sampling technique with the Tabachic & Fidell method. The analysis method used in this study is multiple linear regression analysis using the IBM Statistical Package for Social Sciences (SPSS) Software Version 21. The result of this study show that the effect of implementing halal tourism which consists of knowlage, profession and culture together has a real and positive effect. However, culture is more dominant which has a real and positive effect on the application of halal tourism, with a variable regression coefficient value of 0.677 which means that if culture has increased by one unit, the value of implementing halal tourism will increase by 0.677. increasing the cultural values of the Pamijahan sub-district community can encourage an increase in the development of halal tourism in the region. Keyword: implementation of Halal Tourism, Perception